2020
DOI: 10.1097/phh.0000000000001213
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Group Model Building With the Shape Up Under 5 Community Committee Working to Prevent Early Childhood Obesity in Somerville, Massachusetts

Abstract: Objective: To describe our process of using group model building (GMB) with the Shape Up Under 5 Committee; measure the effects on Committee members; and describe the community-wide health messaging campaign that resulted from the process. Design: Pilot study. Setting: Somerville, Massachusetts. Participants: Members of the Shape Up Under 5 Committee, a multisector group of professionals. Intervention: Research team convened the Committee and facilitated GMB from October 2015 to June 2017. Main Outcome Measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…The Catalyzing Communities project design and methods are described elsewhere [ 25 , 27 ]. In brief, Catalyzing Communities investigates the attributes and processes of newly formed coalitions (the “Coalition-Committee”) that are convened for the study and comprised of stakeholders from an array of sectors (e.g., community-based organizations, community members, hospitals, schools, philanthropy) serving children and their families.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Catalyzing Communities project design and methods are described elsewhere [ 25 , 27 ]. In brief, Catalyzing Communities investigates the attributes and processes of newly formed coalitions (the “Coalition-Committee”) that are convened for the study and comprised of stakeholders from an array of sectors (e.g., community-based organizations, community members, hospitals, schools, philanthropy) serving children and their families.…”
Section: Methodsmentioning
confidence: 99%
“…It is based on the Stakeholder-Driven Community Diffusion Theory, which describes an empirically testable mechanism for promoting community change whereby knowledge of and engagement with childhood obesity within a group of convened stakeholders can diffuse through their social networks and lead to changes in policies, systems, and environments that have been shown impact children’s behaviors and health outcomes [ 28 , 29 ]. Our SDCD-informed intervention employs group model building and technical assistance with convened stakeholders to build knowledge, engagement, and the use of research evidence in community-led actions [ 27 ]. Our initial studies have been shown to increase knowledge of and engagement with childhood obesity prevention efforts among stakeholders [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…This underscores the critical need to engage a broad range of stakeholders relevant to the problem and mobilize their viewpoints and knowledge to achieve a better understanding of the system as a whole. Interviews with key informants and group model building activities are two ways of engaging with stakeholders, the latter enabling their active participation in the process of developing the systems map, leading not only to a more relevant model, but to a communal understanding of the system's form and function and shared vision and insights 2,9,14,37,39,40 …”
Section: An Action‐oriented Framework For Systems Changes For Childhood Obesity Preventionmentioning
confidence: 99%
“…Our research team used the SDCD theory to inform an intervention that targets specific constructs and processes. The intervention was pilot tested ( 21 ) and was then implemented in Cuyahoga County, Ohio; that implementation is the focus of this study.…”
Section: Introductionmentioning
confidence: 99%